Die stand van kliniese evaluering aan Suider-Afrikaanse Universiteite - M. Mulder; M. Viljoen (AOSIS, 1992)
The fact that clinical evaluation is a difficult and complex task of nursing education has been emphasized in the nursing literature since the early seventies. It is, nevertheless, a most important component of the teaching-learning process of nursing students and it has definite advantages. It: * contributes to the improvement of the standard of nursing care * helps to identify problem areas for research and * contributes to high level professional preparation. In the light of these factors the aims of the study were to: * determine and describe the position of clinical evaluation as a component of the teaching of undergraduate students in departments of nursing at universities in Southern Africa; * draw up a proto-theoretical model for clinical evaluation. The second aim will be fully discussed in a follow-up article. The empirical data showed that nursing educationists in Southern Africa are not entirely up to standard regarding the skills required for clinical evaluation.